CHARLES DICKENS’GREAT EXPECTATIONS AS THE REPRESENTATION OF HUMAN GUILT AND SHAME - Indah Sari Karo-Karo (Muse: Jurnal of Art, 2022)
The research discusses guilt and shame as reflected in Charles Dickens’s novel, Great Expectations. This novel portrays guilt and shame as self-conscious and evaluates emotions that occur in people life. This is a library research and applies mimetic approach seing that literary work is an imitation or reflection of presentation of the real life. The analysis is focused on guilt and shame in which Dickens uses an orphan boy, Pip as the representation of thse two feelings. He feels guilty of his snobbery and snobbishness his family and shame of his low origin. These two feelings bring about inner conflict to him but it also gives an enlightenment to evaluate himself. Through research it is concluded that Charles Dickens through his novel Great Expectations vividly portrays guilt and shame in human life. Guilt feeling arises fromreaction of disapproved act while shame is reaction when one feels weak and inferior to others and disappointed about something inside, our basic nature